(untitled) (The Research of Medical Science Review, 2025)
Background: NAFLD is becoming more linked to problems outside the liver, with chronic kidney disease (CKD) being the main extra hepatic result. Similar risk factors that link the two diseases are obesity, insulin resistance and hypertension. Being aware of how NAFLD impacts function in the kidneys leads to faster treatment and helping patients with other diseases. Objectives: to determine the number of NAFLD cases in patients with CKD and to check if renal dysfunction is strongly related to it. Study Design: A cross-sectional observational Study. Place and duration of study: From January 2024 to December 2024 General Medicine Department, Sandeman Provincial Hospital / Bolan Medical College / Hospital, Quetta. Methods: data was collected over 1 Years at a tertiary care hospital. In all, 100 patients diagnosed with CKD had ultrasound examinations and liver function tests to screen for NAFLD. We took the patient’s demographic information, BMI, lipid levels and serum creatinine. All statistical analyses were done with SPSS version 25. The researchers considered a p-value lower than 0.05 as significant. Results: 62 out of 100 CKD patients were also diagnosed with NAFLD. The average age for participants was 52.4 years with a standard deviation of 9.3 years. Those with NAFLD often had both higher BMI and higher levels of triglycerides. A difference we could be certain wasn’t due to chance was found between NAFLD and reduced eGFR (p = 0.021). Results show that more males than females had fasting glucose levels above normal limits. Still, this difference was not statistically significant (p = 0.118). Conclusion: Many CKD patients have NAFLD and it tends to worsen kidney function. Finding NAFLD at an early stage and treating it carefully in CKD patients could help stop or slow kidney disease. Managing the different features of metabolic syndrome through integrative care can help people reach better outcomes.